Construct validity and reliability of a real-time multidimensional smartphone app to assess pain in children and adolescents with cancer. Issue 12 (December 2015) - Stinson, Jennifer N.; Jibb, Lindsay A.; Nguyen, Cynthia; Nathan, Paul C.; Maloney, Anne Marie; Dupuis, L. Lee; Gerstle, J. Ted; Hopyan, Sevan; Alman, Benjamin A.; Strahlendorf, Caron; Portwine, Carol; Johnston, Donna L.
Abstract : Abstract: We evaluated the construct validity (including responsiveness), reliability, and feasibility of the Pain Squad multidimensional smartphone-based pain assessment application (app) in children and adolescents with cancer, using 2 descriptive studies with repeated measures. Participants (8-18 years) undergoing cancer treatment were drawn from 4 pediatric cancer centers. In study 1, 92 participants self-reported their level of pain twice daily for 2 weeks using the Pain Squad app to assess app construct validity and reliability. In study 2, 14 participants recorded their level of pain twice a day for 1 week before and 2 weeks after cancer-related surgery to determine app responsiveness. Participants in both studies completed multiple measures to determine the construct validity and feasibility of the Pain Squad app. Correlations between average weekly pain ratings on the Pain Squad app and recalled least, average, and worst weekly pain were moderate to high (0.43-0.68). Correlations with health-related quality of life and pain coping (measured with PedsQL Inventory 4.0, PedsQL Cancer Module, and Pain Coping Questionnaire) were −0.46 to 0.29. The app showed excellent internal consistency (α = 0.96). Pain ratings changed because of surgery with large effect sizes between baseline and the first week postsurgery (>0.85) and small effect sizes between baseline and the second week postsurgery (0.13-0.32). These findings provide evidence of the construct validity, reliability, and feasibility of the Pain Squad app in children and adolescents with cancer. Use of real-time data capture approaches should be considered in future studies of childhood cancer pain. A video accompanying this abstract is available online as Supplemental Digital Content athttp://links.lww.com/PAIN/A169 . Abstract : Supplemental Digital Content is Available in the Text.The construct validity and internal consistency reliability of a real-time data capture app to assess pain in children and adolescents with cancer has been demonstrated.